Synthesis of a new magnetic-MIP for the selective detection of 1-chloro-2,4-dinitrobenzene, a highly allergenic compound - Uzuriaga-Sánchez, Rosario Josefina [UNESP]; Wong, Ademar [UNESP]; Khan, Sabir [UNESP]; Pividori, Maria I.; Picasso, Gino; Sotomayor, Maria D.P.T. [UNESP] (Elsevier, 2017)
Molecularly imprinted polymers (MIPs) in combination with magnetic nanoparticles, in a core@shell format, were studied for selective detection of 1-chloro-2,4-dinitrobenzene (CDNB), a powerful allergenic substance. Magnetic nanoparticles were prepared by the co-precipitation method and mixed with oleic acid (OA). This material was then encapsulated in three types of hydrophobic polymeric matrix, poly-(MA-co-EDGMA), poly-(AA-co-EDGMA), and poly-(1-VN-co-EDGMA), by the mini-emulsion method. These matrices were used due to their ability to interact specifically with the functional groups of the analyte. Finally, the MIP-CDNB was obtained on the magnetic-hydrophobic surfaces using precipitation polymerization in the presence of the analyte. XRD diffraction patterns suggested the presence of magnetite in the composite and SEM analysis revealed a nanoparticle size between 10 and 18 nm. Under the optimized adsorption conditions, the magnetic-MIP material showed a higher adsorption capacity (5.1 mg g− 1) than its non-magnetic counterpart (4.2 mg g− 1). In tests of the selectivity of the magnetic-MIP towards CDNB, α-values of 2.5 and 10.4, respectively, were obtained for dichlorophenol and o-nitrophenol, two structurally similar compounds, and no adsorption was observed for any other non-analogous analyte. The magnetic-MIP and magnetic-NIP were applied using water enriched with 0.5 mg L− 1 of CDNB, achieving recovery values of 83.8(± 0.8)% and 66(± 1)%, respectively, revealing the suitability of the material for detection of CDNB.
Keywords: 1-Chloro-2,4-dinitrobenzene; Allergenic substances; Biomimetic polymers; Environmental control; Magnetic-MIP; Plastic antibodies